Synthesis, characterization and investigation of dielectric properties of two-armed graft copolymers prepared with methyl methacrylate and styrene onto PVC using atom transfer radical polymerization - Coskun, Mehmet; Seven, Pinar (Elsevier Science Bv, 2011)
Poly(vinyl chloride-co-vinyl diethanolamine) copolymers were synthesized by modification of PVC with diethanolamine. Acylation of -OH groups in the copolymer with alpha-bromoisobutirylbromide gave poly[-vinyl chloride-co-vinyl-bis]2-(2-bromo-2-methylpropanoato)ethyl [amine) as two-armed macroinitiator. A series of grafting studies with methyl methacrylate and styrene was carried out in the presence of the macroinitiator and the catalyst CuBr/2,2'-bipyridyl (bpy) at 110 degrees C. FT-IR Spectra of all the polymers were recorded for the structural characterization, and (1)H and (13)C NMR spectra were also used in the characterization PVC-graft-methyl methacrylate. During the grafting reaction at 110 degrees C, the number-average molecular weight of the macroinitiator increased from 63,700 (polydispersity 2.17) to 159,000 (polydispersity 1.40) at 20 h in case of methyl methacrylate, and to 86,900 (polydispersity 1.70) at 48 h in case of styrene. The thermally stability of PVC modified with diethanol amine and the macroinitiator was similar that of PVC as initial decomposition temperature, but the graft copolymers showed higher thermal stability than PVC. While the glass-transition temperatures of PVC. PVC modified with diethanol amine and the macroinitiator showed a glass-transition temperature at around 91 degrees C, the graft copolymers of methyl methacrylate and styrene showed at 120 degrees C and 98 degrees C. respectively. The dielectric features of the macroinitiator and the graft copolymers against the frequency at the room temperature were examined. Dielectric constant of macroinitiator was calculated as 4.76 at 100 Hz. Dielectric features of the polymers against the temperature at three different frequency was examined. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: PVC; Methyl methacrylate; Styrene; Graft copolymer; Dielectric properties; ATRP